EU-Russia Educational Cooperation as a Democracy Promotion Mechanism - Ekaterina Gorbunova (Journal of Contemporary European Research, 2011)
The idea of understanding and assessing the EU’s role in promoting democratic values in the neighbourhood has acquired a central place in the EU’s external relations discourse. At the same time, in the literature on democratisation, education is conventionally considered one of the key prerequisites of successful democratic transition and consolidation. Still, a rich body of democracy promotion literature and Europeanisation studies never discuss education as a possible mechanism of democratic socialisation. The article aims to fill this gap by bringing together these two different scholarly traditions and by looking at EU-Russia educational cooperation as a mechanism to promote democratic values. The following propositions are advanced on the basis of the analysis: (1) democracy promotion is both implicitly and explicitly present in the EU-Russia educational policy discourse; (2) the level of education is a valid predictor of more democratic attitudes in Russia and, hence, should be considered a strong factor of a country’s democratisation.